Antifungal Activity and Cytotoxicity of Imidazole- and Morpholine-Based Lysosomotropic Detergents - Diana Hodyna; Vasyl Kovalishyn; Yurii Shulha; Olena Trokhimenko; Olesya Aksenovska; Sergiy Rogalsky; Larysa Metelytsia (Innovative Biosystems and Bioengineering)
Background. The spread of infectious diseases caused by drug-resistant bacteria and fungi, especially nosocomial strains, is currently considered a serious medical problem. It is known that the fungus Candida albicans is the most common causative agent of candidal infection, including the severe type. The emergence and rapid formation of drug resistance, as a risk factor in the treatment of oncological diseases burdened by candidal infection, requires new therapeutic approaches, including the study of synthetic bioregulators with antifungal and anticancer efficacy.